Performance as a Research Instrument: An Example from the Western European Baroque - Edward C. Van Ness (PROMUSIKA : Jurnal Pengkajian, Penyajian, dan Penciptaan Musik, 2017)
In this paper, I discuss performance as a research instrument in Western European classical music.  I describe considerations and process leading to my performance of Corelli Op. 5 no. 12 "Follia" in the Indonesian Chamber Music Festival 2011 at ISI Yogyakarta Concert Hall.  Corelli's Follia (La Folia), as it is commonly known, is a canonized work which opens many professional violinist's recital programs. Its real identity has become marginalized and transformed through rather blind reliance on 19th-century editions by violinists who wished to adopt it to "mainline" romantic concepts of style and performance. This process of adaption has been characteristic of European classical music for centuries. Works of earlier times were reshaped both in performance and in print editions to fit prevailing musical tastes.  I chose to approximate an appropriate ensemble with modern instruments. Using a constructivist approach, I employed aspects of Baroque performance practice, especially in ornamentation and embellishment, along with manipulation of rhythmic elements and in a more spontaneous, and consciously contemporary manner.  I take the opportunity to contribute to productive dialogue regarding the role of performance at Music Department, the Faculty of Performing Arts, Yogyakarta Indonesian Institute of the Arts, and qualitative research. I seek to open up our discourse to a wider understanding beyond the persistent positivist continues to approach the academic world in Indonesia as the only platform for research theory and method.  I suggest that this performance, like any other, is an informed adventure across time and space and that ethnomusicology and music are no longer separate worlds.